Morphometric Analysis of Anura in Rajolelo Forest Park ‎Bengkulu Province - Reska Ayu Muslimah; Mega Sari Apriniarti; Kasmiruddin Kasmiruddin (Yayasan Darussalam Bengkulu, 2026)
This study aims to analyze the morphometric characteristics of Anura found in Rajolelo Forest Park, Central Bengkulu. Data collection was conducted from November 2025 to January 2026 using the Visual Encounter Survey (VES) method in two habitat types, namely secondary forest and lakeshore. Each individual found was identified and measured using 13 morphometric characters with the help of a caliper. The results showed that the Anura community found consisted of three families, namely Dicroglossidae, Ranidae, and Rhacophoridae, with five species and a total of 20 individuals. Morphometric analysis showed that there were variations in body size and limb proportions between species related to habitat differences. Species found in water tend to have larger body sizes, while species living in vegetation or secondary forests have longer limbs that support the ability to jump and move in vegetation. Thus, morphometric variations in Anura indicate morphological adaptations to different habitat conditions.